Object-Oriented Programming and Objectivist Epistemology: Parallels and Implications. - Reed, Adam (Journal of Ayn Rand Studies (Journal of Ayn Rand Studies Foundation))
Reed argues that the architectures of knowledge representation in Object-Oriented Programming (OOP) and in Ayn Rand's Objectivist epistemology are exactly isomorphic, and were first proposed at about the same time. These similarities did not result from mutual influence, but from the need to represent knowledge, in both systems, in accordance with the same facts of reality. Thanks to the isomorphism of knowledge representation in the two systems, logical techniques developed in the context of OOP, such as scope-tracking and inheritance, are directly usable and useful in objective logic based on Objectivist epistemology.